Effectiveness of Jacobson Progressive Muscle Relaxation Technique on Low Back Pain among Sanitary workers working in selected hospitals at Kanyakumari dist. - H. Magilin Sheeba; .Dr. Chandra T; Dr. Arzta Sophiya (The Bioscan, 2024)
Background: Low back pain is one of the common musculoskeletal health problems that occur most commonly among all Health workers. Different researches showed that health care team members are suffering from low back pain due to many factors. This research was conducted to find the prevalence and contributing factors of low back pain among sanitary workers and provide Jacobson Progressive Muscle Relaxation. Method: The Pre experimental study was done among 30 sanitary workers by using purposive sampling method. Semi structured self-administered questionnaire with single and multiple responses was administered among sanitary workers after taking informed consent. And using Oswestry low back disability questionnaire (OLBDQ) their back pain was assessed in pre test after that Jacobson Progressive Muscle Relaxation Technique was taught to the sanitary workers for four weeks then post test was conducted with the same scale. Results: After four weeks of performing Jacobson Progressive Muscle Relaxation Technique on the lower Back, and according to the results of the pre-test and posttest a significant Decrease in back pain level was observed (P < 0.05) and reduction in pain level Conclusion: Jacobson Progressive Muscle Relaxation Technique on the lower Back showed a significant effect on the increased balance and pain Reduction. Thus the Recommended exercises can be suggested according to the type of exercises as a factor for increasing static and dynamic balance.